Awaken therapy : recreating lost space through therapeutic landscape at Hospital Tuanku Ja’afar Seremban, Negeri Sembilan - Abdul Rahman, Muhammad Nasir Mukhriz (2018)
Today, in Malaysia, green spaces within the healthcare facilities in not that impressive in order the healing process to be deliver to the users who using the space. Particularly, green spaces outside the hospital are not only to be essential but also valuable. However, the evidence is clear that garden and nature elements could help in reduction of stress, invoke senses of users and physical attractiveness of a healthcare landscape design contribute to positive satisfaction and loyalty of patients, staff and visitors. In this study also discussed, the importance of cognitive psychology and senses of human through therapeutic landscape elements is vital in order the healing process to occur. Through collection of data and information during the inventory and analysis, there are several main issues may be a barrier for the therapeutic landscape to be implement at Hospital Tuanku Ja’afar Seremban. Questionnaire distributed through the hospital to gained more evidences to strengthen the support and act as guidance to solving the issues by considering users’ needs and translate the studies into a design that will be apply at the hospital area.